Nutritional immunomodulation of Atlantic salmon response to Renibacterium salmoninarum bacterin - Emam, Mohamed; Eslamloo, Khalil; Caballero-Solares, Albert; Lorenz, Evandro Kleber; Xue, Xi; Umasuthan, Navaneethaiyer; Gnanagobal, Hajarooba; Santander, Javier; Taylor, Richard G.; Balder, Rachel; Parrish, Christopher C.; Rise, Matthew L. (Frontiers in Molecular Biosciences, 2022)
We investigated the immunomodulatory effect of varying levels of dietary ω6/ω3 fatty acids (FA) on Atlantic salmon (Salmo salar) antibacterial response. Two groups were fed either high-18:3ω3 or high-18:2ω6 FA diets for 8-weeks, and a third group was fed for 4-weeks on the high-18:2ω6 diet followed by 4-weeks on the high-18:3ω3 diet and termed “Switched-diet”. Following the second 4-weeks of feeding (i.e., at 8-weeks) all groups were sampled for FA analysis. Then fish were intraperitoneally injected with either a formalin-killed Renibacterium salmoninarum bacterin (5 × 107 cells mL-1) or phosphate-buffered saline, and head kidney tissues were sampled at 24 h post-injection for gene expression analysis. The qPCR analyses of twenty-three genes showed that both high-ω6 and high-ω3 groups had similar bacterin-dependent induction of some transcripts involved in lipid metabolism (ch25ha and lipe), pathogen recognition (clec12b and tlr5), and immune effectors (znrf1and cish). In contrast, these transcripts did not significantly respond to the bacterin in the “Switched-diet” group. Concurrently, biomarkers encoding proteins with putative roles in biotic inflammatory response (tnfrsf6b) and dendritic cell maturation (ccl13) were upregulated, and a chemokine receptor (cxcr1) was downregulated with the bacterin injection regardless of the experimental diets. On the other hand, an inflammatory regulator biomarker, bcl3 was only significantly upregulated in the high-ω3 fed group and a C‑type lectin family member (clec3a) was only significantly downregulated in the Switched-diet group with the bacterin injection (compared with diet-matched PBS injected controls). Transcript fold-change (bacterin/PBS) and FA associations highlighted the role of DGLA (20:3ω6; anti-inflammatory) and/or EPA (20:5ω3; anti-inflammatory) versus ARA (20:4ω6; pro-inflammatory), as representative of the anti-inflammatory / pro-inflammatory balance between eicosanoid precursors. Also, the correlations revealed associations of FA percent and ratios with several eicosanoid and immune receptor biomarkers (e.g. DGLA/ARA significant positive correlation with pgds, 5loxa, 5loxb, tlr5, and cxcr1). In summary, dietary FA profiles and/or regimen modulated the expression of some immune-relevant genes in Atlantic salmon injected with R. salmoninarum bacterin. The modulation of Atlantic salmon responses to bacterial pathogens and their associated antigens using high-ω6/high-ω3 diets warrants further investigation.